Odpowiedzi

2009-11-08T15:13:42+01:00
A)3*(½)⁻² - 4*(1/3)⁻¹=
3*(2)^2 - 4*(3)^1=3*4 - 4*3 = 12 - 12 = 0

b)5*(2/3)⁻¹ +2*(1/5)⁻²=
5*(3/2)^1 + 2*(5)^2=15/2 + 2*25 = 15/2 + 50 = 15/2 + 100/2 = 115/2 = 57 i 1/2

c)(2/3)⁻²: (1/4)²=
(3/2)^2:(1/16)= 9/4*16/1=9/1*4/1=36

od d do f zapisz poprawnie rownania
d)(3/4)⁻² * 4⁻³ +3 : (2/3)⁻¹ - (1/6)²=

e)(4 1/2)⁻¹ * (2/5)⁻² - 3 * (1/2)⁻² - (2 4/7)⁻¹=
f)(3⁻¹+2⁻²)⁻²+4⁻¹:(2/7)⁻²+ 2/49=
1 2 1
2009-11-08T15:32:40+01:00
A)3*(½)⁻²-4*(⅓)⁻¹=3*2²-4*3¹=3*4-4*3=12-12=0
b)5*(⅔)⁻¹+2(⅕)⁻²=(3/2)¹+2*5²=5*3/2+2*25=7,5+50=57,5
c)(⅔)⁻²:(¼)²=(3/2)²:(1/16)=9/4*16=36
d)(¾)⁻²*4⁻³+3:(⅔)⁻¹-(⅙)²=(4/3)²*(¼)³+3:(3/2)-(1/36)=(16/9)*(1/64)+3:3/2)-(1/36)=(1/36)+2-(1/36)=2
e)(4½)⁻¹ *(⅖)⁻²-3*(½)⁻²-(2 4/7)⁻¹= (2/9)*(5/2)²-3*2²-(7/18)=(5/9)-3*4-(7/18)=(10/18)-12-(7/18)=(3/18)-12=11⅚
f)(3⁻¹+2⁻²)⁻²+4⁻¹:(2/7)⁻²+2/49=(⅓+(½)²)⁻²+¼:(7/2)²+(2/49)=(⅓+¼)⁻²+¼:(49/4)+(2/49)=(4/12+3/12)²+(1/49)+(2/49)=(7/12)⁻²+(3/49)=(12/7)²+(3/49)=(144/49)+3/49=147/49=3
1 2 1